Education Secularism in Indonesia and Society's Interpretation - Rima Nur Ekawati (LP3M Pascasarjana STAI Ibnurusyd, 2025)
Education produces an understanding or thought that can turn people into human beings who can distinguish between good and bad. The understanding of secularism has various impacts on the life of the state and this applies to all countries in the world if they want to apply this understanding. In Indonesia, secularism in education has occurred for a long time, namely during the 19th century when the colonizers ruled the world, they brought tremendous influence on the government order and spiritual order in this country. General and religious education are not balanced and more prominent in general education alone is emphasized. However, in Islam, this is a wrong understanding because it excludes God as the almighty Essence. This study aims to understand the history, the spread of secularism in education in Indonesia, and what steps should be taken in solving this problem. By using a literature study and descriptive approach, it turns out that understanding the secularism of education in Indonesia has a significant impact in the sense that we are difficult to unite if there are differences in education and there is a need for evaluation with a situation that has already taken root.